Design of Permeable Acoustic Metamaterial Panels to Reduce Blade Passing Frequency Noise 날개 통과 주파수 소음 저감을 위한 통기성 음향 메타물질 패널 설계 - Kim, Beom Jin; Lee, Jin Woo (Transactions of the Korean Society of Mechanical Engineers, A, 2024)
We propose a method for designing an acoustic metamaterial panel that passes the high-temperature fluid generated from a cooling system fan while attenuating blade-passing frequency noise. The unit cell of the proposed acoustic metamaterial comprises three 1/4 wavelength tubes, the standard length of which is determined by conSidering the wavelength corresponding to multiples of the blade-passing frequency. The designed units are arranged in the direction of fluid penetration to widen the noise reduction frequency band. Additionally, the length of each wavelength tube within the arranged unit cells varies linearly, ensuring effective noise attenuation can be maintained even if the blade-passing frequency fluctuates owing to the fan's rotational speed. The length of each wavelength tube is determined from a dispersion curve, and the noise reduction performance of the designed unit cells is evaluated using their transmission loss curves. The proposed design method can be applied to reduce blade passing frequencies in various fan configurations.
Keywords: % reductions; Acoustic metamaterial; Acoustic metamaterial panel; Blade passing frequency; Blade passing frequency noise; Dispersion curves; Highest temperature; One-quarter wavelength tube; Quarter-wavelength; Unit cells; Acoustic Metamaterial Panel; Blade Passing Frequency; Dispersion Curve; One-Quarter Wavelength Tube; Unit Cell